Il sistema rurale. una sfida per la progettazione tra salvaguardia, sostenibilità e governo delle trasformazioni Milano, ottobre 2004 - Marzorati, Paola (Ri-Vista. Research for landscape architecture, 2015)
Lombardy Region with University Politecnic of Milan organized an international conference “The rural system. A challenge for planning between protection, sustainability and changes’ management”, in Milan at 13th-14th October 2004. This meeting’s efforts will be addressed in verifying if and how the values of multi-functionality practice can be extended, in the short period, to most part of the rural land. In order to obtain this goal the meeting will focus on recognizing the characters of agricultural land, deepening ecological, socio-economical functions and preserving rural landscape ones as part of a greater and more comprehensive planning process based on sustainable design and on a "good policy" approach. This items and issues will be focused exploring some Italian and international best-practices.